2020
DOI: 10.1109/access.2020.3028370
|View full text |Cite
|
Sign up to set email alerts
|

Review of Android Malware Detection Based on Deep Learning

Abstract: At present, smartphones running the Android operating system have occupied the leading market share. However, due to the Android operating system's open-source nature, Android malware has increased dramatically. Malware can steal user privacy and even maliciously charge fees and steal funds. It has posed a severe threat to cyberspace security because traditional detection methods have many limitations. With the widespread application of deep learning in recent years, the method of detecting Android malware usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 81 publications
0
31
0
1
Order By: Relevance
“…Due to API changes, and now able to capture previously unseen activities. The results also demon state that EveDroid is more accurate and robust to malware evolvement compared to existing detection systems [93]. Classification utilizing machine learning was an important class of malware security solutions.…”
Section: Fig 2 Architecture Of Droid Deep [57]mentioning
confidence: 77%
“…Due to API changes, and now able to capture previously unseen activities. The results also demon state that EveDroid is more accurate and robust to malware evolvement compared to existing detection systems [93]. Classification utilizing machine learning was an important class of malware security solutions.…”
Section: Fig 2 Architecture Of Droid Deep [57]mentioning
confidence: 77%
“…e authors in [7][8][9] analysed the Android security mechanism and typical malware detection methods. e authors in [10][11][12] focused on applying deep learning algorithms such as Restricted Boltzmann Machines, Convolutional Neural Network, Deep Belief Network, Recurrent Neural Network, and Deep Autoencoder to malware detection and analysed the advantages and results achieved. e authors in [13] is mainly concerned with the analysis of Android malware variants' detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…K. Liu et al [5] presented research on machine learning-based Android malware detection conducted up to the year 2020. In addition, Z. Wang et al [6] published a review of Android malware detection applying deep learning. Rana et al [7] also found an algorithm that best classifies malware through experiments, aiming to find the most effective malware detector among 12 different machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%